Risk factors and complications of tuberculosis due to treatment abandonment (Research, Society and Development, 2020)
This work aims to identify and analyze risk factors, complications and profile of individuals in the event of abandonment of tuberculosis treatment. This is an integrative review of the literature of studies between 2015 and 2020. To survey the studies, a source made available by consulting the database of the Virtual Health Library with the descriptors “Tuberculosis”, “Risk Factor” and “ Treatment Adherence ”. Authors corroborate that risk factors such as consumption of licit and illicit drugs, clinical improvement during treatment, adverse effects of medications and discontinuity of care influence the lack of adherence to treatment, as well as the profile of men, young adults and low education levels. the most cited in studies. There was a need for health services to seek new strategies for their developed practices, humanizing their assistance and strengthening the bond with the user.